Intellectual Capital and Good Corporate Governance Structure on Financial Performance at Islamic Commercial Banks in Indonesia - Muhibddin, Muhibddin; Mufraini , M. Arief (LPPPM STAI Darul Hikmah Bangkalan, 2022)
This research article was intended to determine the significance of the influence provided by factors on the financial performance of Islamic commercial banks, which include Intellectual Capital (IC) and Good Corporate Governance (GCG). The subjects involved in this research were Islamic banking in Indonesia which had published its 2019 financial reports. The samples in this research were determined by purposive sampling method, which was based on the criteria that had been determined in this research. Regarding to the sample selection process, there were only 13 companies that published 2019 financial statements. This research was successfully carried out by using Component Based SEM with PLS as a data processing and analysis tool. The results of this research inferred that there was a positive influence of Intellectual Capital and Good Corporate Governance Structure on the Financial Performance of Islamic Commercial Banks in Indonesia. This research provided positive implications for Islamic banks that have seriously managed good Intellectual Capital by implementing a Good Corporate Governance structure that is simultaneously able to increase the company’s financial performance.